Asset price fluctuations in Japan: 1980 - 2000 - Tomoyuki Nakajima (Brown University, Department of Economics, 2003)
A notable feature of the Japanese economy in the last two decades is the large fluctuations in asset prices. We examine whether they can by accounted for by a stochastic growth model with habit persistence and costly capital adjustment. For the real estate price, people's expectations on the trend growth rate in the future plays a crucial role. In particular, our model with adaptive expectations about future productivity growth can reproduce the aggregate land price. However, even with habit persistence and costly capital adjustment, a substantial portion of the stock price fluctuations is left unexplained, and a puzzle remains. Our result suggests that the price of installed capital is close to zero or that people don't take into account the value of capital when trade shares.
Keywords: E32; E37; G12; O40; O53; 330; Japanese economy; land prices; stock prices; adaptive expectations; productivity growth; Börsenkurs; Bodenpreis; Adaptive Erwartung; Produktivität; Stochastisches Wachstumsmodell; Japan